Stabilization of empty fruit bunch with addition of palm oil mill effluent during vermicompost - Astimar Abdul Aziz (Malaysian Palm Oil Board, 2015)
The feasibility of vermicomposting technology to stabilize the oil palm fibre waste (EFB) mixed with a bulking agent (POME) in different proportions viz. 100% (V1), 90% (V2), 80% (V3), 70% (V4), 60% (V5), and 50% (V6) was tested using composting earthworm Eisenia fetida for 84 days. The vermitreated sludge was evaluated for different physico-chemical parameters and all vermibeds expressed in pH gradually increased and remained in the range 7.9-8.5, reduction of C/N ratio (69.7-87.4%), and an increase in total kjeldahl nitrogen (TKN) (16.67-97.53%), available P (TP) (54.55-80.0%) as well as exchangeable K (TK) (50.0-80.0%). Data suggested that inoculated earthworms could maximize the decomposition and mineralization rate, if sludge is used with appropriate bulking material for earthworm feed. Vermicomposting also caused significant increases in total concentration of metals but still in the standard range of nutrients in vermicompost: Zn (0.560.69 mg/kg), Fe (15.60-22.79 mg/kg), Mn (1.26-2.01 mg/kg) and Cu (0.030.07 mg/kg) in vermicast. The feasibility of earthworms to enhance the nutrient profile in sludge might be useful in sustainable land restoration practices at low-input basis.